VARIASI DOSIS MOL (MIKROORGANISME LOKAL) HASIL FERMENTASI LIMBAH SAYUR UNTUK PENGAYAAN MEDIA KULTUR Daphnia magna - Fauzana, Noor Arida; Adriani, Muhammad; Ansyari, Pahmi; Slamat, Slamat; Darusman, Febri Anugrah (Program Studi Akuakultur, Universitas Bangka Belitung, 2025)
MOL (Local Microorganisms) is a solution resulting from fermentation from the decay of organic materials, the solution is useful to helping the process of decomposition of organic materials. MOL has the potential to be a bioactivator in fermentation. This study aims to analyze the abundance of Daphnia magna populations cultured on media with the addition of MOL with different doses. The research was carried out at the Fish Nutrition Laboratory, Faculty of Fisheries and Marine Sciences, Lambung Mangkurat University, Banjarbaru City, South Kalimantan Province. The MOL used comes from fermented vegetable waste of cabbage, cauliflower leaves and mustard greens that are fermented for 14 days. This study used a Complete Random Design (CRD) of 4 treatments and 3 replicates with a MOL dose of 0 mL/L (K), 0.5 mL/L (A), 1 mL/L (B), and 1.5 mL/L (C). The parameters observed were population abundance, population growth rate, maximum population growth of Daphnia magna, and water quality. The study showed the best results in Treatment C, namely an abundance of 2453.33±68.06 ind/L, a growth rate of 51.44±0.134% and the maximum growth of the Daphnia magna population occurred on day 8. The results of the analysis of nutrient quality from MOL and the quality of culture media water are very supportive in the growth of Daphnia magna. The application of MOL of vegetable waste fermented from cabbage, cauliflower leaves and mustard greens waste as much as 1.5 mL/L in culture media can be considered in the enrichment of culture media for the growth of Daphnia magna.